Faculty of health sciences students’ views and preferences on organic foods - Kocaçal, Elem; İrkin , Reyhan and Erkin, Özüm and Konakçı , Gülbin (Progress in Nutrition, 2022)
Summary. Objectives: To determine the faculty of health sciences students’ opinions and preferences regarding organic foods. Material and Methods: This descriptive study was conducted at Faculty of Health Sciences in a Turkish University in 2020. The universe of the study consisted of 334 volunteer students. Data were collected using a self-administered questionnaire. Results: Of the students 40.4% of the participants indicated that they consumed organic foods every week. Although the department and class of the students within the scope of the study did not affect the preferences and opinions about organic foods in general (p > 0.05); the relationship between the department and the frequency of organic food consumption (X2 = 46.542; df = 12; p = 0.000) and the status of reading labels on organic food packages (X2 = 10.114; df = 3; p = 0.018) was found to be significant. Conclusion: The majority of university students consumed organic food and had an awareness about organic nutrition. In the future studies, in addition to the variables examined in this study, we recommend examining different student populations.